SAT-068 Bewilderment! Sex Chromosome Non-Invasive Prenatal Screening (NIPS) Results Differ from Phenotype and Postnatal Karyotype - Perez-Garcia, Eliana Melissa (J Endocr Soc, 2020)
Background NIPS uses cell-free DNA in maternal serum to identify fetal aneuploidies including sex chromosome aneuploidies (SCA).(1) Despite reports of high sensitivity and specificity, NIPS results, phenotype, and postnatal karyotype may be inconsistent. This situation generates parental anxiety and physician apprehension especially when the apparent genital phenotype differs from the NIPS result. We report four cases involving genotype-phenotype discordance in infants with disorders of sex development (DSD). Case 1: Female infant with complex congenital heart disease had inconclusive NIPS results. Postnatal karyotype was 46,XY karyotype (positive for SRY gene). Ultrasound [US] confirmed female internal genitalia. Postnatal karyotype on uncultured peripheral blood cells with FISH showed mosaicism [46,XY (85%)/45,X (15%)]. Case 2: Female infant conceived via IVF had 46,XY karyotype on NIPS. Prenatal and postnatal US showed female internal genitalia. Postnatal results showed 46,XX karyotype and Urine FISH analysis reported XX in all examined cells. Maternal karyotype is 46,XX; maternal FISH results are pending. Case 3: NIPS reported 45,X. Prenatal US showed male external genitalia. Postnatal exam showed male phenotype with right gonad in inguinal region. Cord blood karyotype and FISH analyses showed mosaicism [45,X (56%)/46,XY (44%)] with 4 different Y chromosome rearrangements. Urine FISH showed mosaicism [45,X (95%)/46,XY (5%)]. Testosterone and AMH concentrations were normal. Case 4: NIPS reported 46,XY karyotype. Prenatal US showed normal female genitalia. Postnatal physical exam revealed low set ears; additional studies revealed horseshoe kidney and atrial septal defect. Cord blood showed mosaicism [45,X (90%)/46,XY (10%)]. Conclusion Discrepancies between NIPS and postnatal karyotype occur more commonly with SCA than for autosomal aneuploidies.(2) Such inconsistencies generate anxiety regarding sex of fetus, suggest a DSD diagnosis, and warrant additional prenatal and postnatal investigations. Testing to prevent missed detection of sex chromosome mosaicism is necessary. Early diagnosis of DSDs benefits the infant and the family. In some instances, NIPS expose undiagnosed maternal factors.(3) Most importantly, communication involving parents and both prenatal and postnatal health care providers is essential to promote timely holistic health care for the infant and family. References 1.Palka C et al., Eur J Obstet Gynecol Reprod Biol X. 2019; 3:100050 2.Ramdaney A et al., Prenat Diagn. 2018;38:841 3.Richardson EJ, et al., Prenat Diagn. 2017;37:1298 Footnotes